Triple primary cancers of the head and neck: case report and literature review. Issue 6 (June 2014) - Adams, M; Caffrey, R
Abstract Background: Coincident thyroid and head and neck squamous cell carcinomas are rare. This paper presents a case of synchronous laryngeal squamous cell carcinoma, follicular thyroid carcinoma and micropapillary thyroid carcinoma. Methods: A PubMed search was performed for articles describing synchronous thyroid and head and neck squamous cell carcinomas, using the search terms 'thyroid cancer', 'cancer of the head and neck', 'synchronous' and 'synchronous neoplasm'. Results: The literature suggests that the head and neck squamous cell carcinoma stage is a better predictor of outcome than the extent of surgical treatment of the thyroid gland in synchronous malignancies. Conclusion: The decision regarding surgical treatment of the thyroid in synchronous thyroid and head and neck squamous cell carcinomas should take several factors into account. The head and neck squamous cell carcinoma stage is the strongest predictor of outcome, although patient-related factors and the location of malignant thyroid tissue may also affect management.